Effects of Planting Dates and Floral Preservatives on Spike Qualities of Gladiolus (Gladiolus grandiflorus) - Suneetha S (Department of Horticulture, College of Agriculture, 1994)
Investigations were carried out at the Department of Horticulture, College of Agriculture, Vellayani during 1992-93 to gather information on the effect of six planting dates at monthly intervals from mid-August to mid-January on the general performance of three gladiolus cultivars. A post-harvest study was also conducted to find out the effect of seven holding solutions on the post-harvest spike characteristics. Studies revealed that corms planted during October were the earliest to complete sprouting. October plantings also produced the tallest plants with maximum leaf number and leaf area. Delayed plantings took more time to attain 100 per cent sprouting and the plants were shorter with less number of leaves and leaf area. The earliest plants to complete spike emergence were the ones planted during November. Among the three cultivars tested, Oscar was the earliest to sprout and Vinks Glory the latest. Maximum plant height, leaf number and leaf area were recorded in the cultivar Vinks Glory. Vinks Glory also produced the maximum number of tillers per plant. Her Majesty was the earliest of the three cultivars to complete flowering, while Vinks Glory took the longest time. Maximum susceptibility to Fusarium wilt was exhibited by the cultivar Her Majesty, whereas Vinks Glory was the least susceptible. Observations on the effect of planting dates on spike characteristics indicated that September plantings registered the maximum spike and rachis lengths. In general, delayed planting resulted in reduced spike and rachis length, floret size and number of florets per spike. Early plantings done in August September and October also produced the maximum number of florets per spike and floret size. The longest spikes with the maximum rachis length, number of florets and floret size were observed in Oscar. The spikes of Oscar also recorded the maximum girth of spike stalk. Early plantings done in August, September and October increased the time taken from spike emergence to opening of first floret, blooming period and vase life of spikes. Delayed planting produced spikes witch were inferior in this respect. Vinks Glory was the cultivar with spikes of maximum blooming period and vase life. Weight of corms produced was highest in the cultivar vinks Glory and lowest in Her Majesty. Her Majesty registered the maximum number of cormels per plant while Oscar produced the maximum cormel weight per plant. Delayed plantings resulted in a reduction of number of cormels per plant.